Pembuatan dan pengujian turbin propeller dalam pengembangan teknologi pembangkit listrik tenaga air piko hidro (PLTA-PH) dengan variasi debit aliran - Henanto Pandu Dewanto; Dwi Aries Himawanto; Sukmaji Indro Cahyono (Jurnal Teknik Mesin Indonesia, 2017)
Hydroelectric power plants (hydropower) with a power generated capacity of less than 5 kW called "Pico Hydro" (hydropower-PH). Pico Hydro is one of the renewable energy sources that are environmentally friendly. In this study aims to: (1) the manufacture hydropower plants Pico Hydro energy-efficient, renewable and environmentally friendly; (2) determine the efficiency of the turbine with the testing of flow variation; (3) determine the efficiency of generator. Designing and making portable water turbines are easily in the manufacture, operation, and maintenance and has a high efficiency and effectiveness that can use the method of reverse engineering. The production process is performed to create a turbine by the lathe and welding processes. While the materials used are mild steel. Results of this study were found that: (1) the manufacturing process of hydropower plants Pico Hydro can be performed easily by the public; (2) the type of turbine used in hydropower-PH testing is a propeller turbine with 4 blades; (3) flow measurement with V-Notch method showed the following actual debit are 5.38 x10-3 (m3/s), 6.62 x10-3 (m3/s), 7.69 x10-3 (m3/s) and 8.84 x10-3 (m3/s. Turbine efficiency is 3.59 %, 4.26 %, 5.66 % and 7.54 %. The efficiency of the generator has a value of 39.31 %, 40.51 %, 32.55 % and 30.45 %.